Phytochemical screening, antibacterial, anti-biofilm and quorum sensing inhibiting activity of Alpinia nigra leaf extract against infectious pathogen Pseudomonas aeruginosa PAO1. (January 2023) - Gupta, Manish Kumar; Singh, Rashmi; Rangan, Latha
Abstract: The recurrent cycles of several bacterial diseases are an endorsement of the formation of biofilms that are intractable to antibiotic therapy. Biofilm-associated diseases have affected millions of people worldwide and are unassailable due to frequent changes of surface antigens and gene expression. Therefore, there is a need to find out an alternative approach to cure biofilm infections. Plant-derived bioactive compounds and their derivative have shown a significant role in combatting bacterial infection. In this scenario, we performed phytochemical screening of ethyl acetate leaf extract (L-EtAc) of Alpina nigra and antibacterial, anti-biofilm activity towards Pseudomonas aeruginosa PAO1 . Antibacterial and growth curve analysis of bacterial cells confirmed the significant bacterial cell death in L-EtAc treated sample. Relatively less biofilm formation was observed in the treated sample as revealed through fluorescence microscopy. Further, quorum-sensing inhibition was observed by applying a similar concentration of L-EtAc on Chromobacterium violaceum bacteria. The interaction between the biofilm-forming protein and phytochemical constituent was validated through in-silico analysis and further confirmed with qRT-PCR. The qRT-PCR data revealed reduced lasI, lasR, lasB, rhlI, rhlR and rhlA gene expression, which may be directly associated with biofilm and extracellular matrix formation. This study might be helpful for the development of new natural product for curing biofilm-associated disease. Graphical abstract: Image 1 Highlights: The A. nigra leaf extract (L-EtAc) displayed inhibiting potential of QS signaling. L-EtAc played a vital role in anti-biofilm activity towards Pseudomonas aeruginosa. The qRT-PCR data revealed reduced biofilm gene expression. This study might be helpful for curing biofilm-associated diseases.